“Elaboración de fideos utilizando puré de fréjol variedad huasca poroto (phaseolus vulgaris) como sustituto parcial de la harina de trigo” - Garcia Saavedra,Robinson (1995)
This research partly replace wheat by ~ l bean in the preparation of noodles and in this way promote the production and consumption of pasta made partially with regional inputs. In this sense they worked with the national variety of bean huasca bean (Phasecilus vulgal "is), wheat flour and other ingredients purchased at our local markets proceeded firstly analyze the raw processing beans huasca, wheat flour) to know its characteristics physical-chemical, considering that the other raw materials and supplies showed characteristics standards , so it was not necessary and go actor izar l cas. The puree of beans was retrieved following the stages. Cooking, drain/cooled and grindDefinitive noodles processing flow, type and urges, is by stages: formulation, mixing/kneading, cooking, loin, cut and dried. The noodles were dried using a solar dryer ca...